EMPOWERMENT OF STATE CIVIL APPARATUS AT THE OFFICE OF THE STATE CIVIL SERVICE AGENCY REGIONAL IX JAYAPURA - Terianus L. Safkaur (Jurnal Scientia, 2023)
This study aims to analyze the empowerment of civil servants at the BKN Regional IX Jayapura office and to identify obstacles to the empowerment of civil servants at the BKN Regional IX Jayapura office. This research uses qualitative methods. Key informants and informants in this study were carried out to the Head of Field, Section Head and several other employees. Data collection techniques are carried out through documentation and interviews/interviews. The results of the study, including 4 indicators that became a reference for research, namely apparatus knowledge, that apparatus knowledge is different because everyone must have differences in any aspect (for example patterns of thought and opinion) but in the office for civil servants who want to continue their study will be given the authority to increase the knowledge, performance and quality of the employees themselves, with a note that the costs are borne by the office not from the office. Apparatus skills, a skill of an ASN is indeed needed, so that employees can complete tasks quickly and well, so it is important for an ASN to attend a training or training, because with the training or training, the work can run as desired. However, in the office only a few employees have attended training or training. Attitudes of Apparatus Towards Their Duties, Attitude of Apparatus towards Their Duties Has Followed the Existing Tupoksi, therefore almost every employee who participates in training is adjusted to their respective tupoksinya because then knowledge of their tupoksinya increases and their attitude and quality of work are better than before.